2012
DOI: 10.5812/hepatmon.6212
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Necrotic Nodules of the Liver: Histology and Diagnosis With CT and MRI

Abstract: BackgroundA solitary necrotic nodule (SNN) of the liver is an uncommon lesion, which is different from primary and metastatic liver cancers.ObjectivesTo analyze the classification, CT and MR manifestation, and the pathological basis of solitary necrotic nodule of the liver (SNN) in order to evaluate CT and MRI as a diagnosing tool.Patients and MethodsThis study included 29 patients with liver SNNs, out of which 14 had no clinical symptoms and were discovered by routine ultrasound examinations, six were found b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
1
14
1
1
Order By: Relevance
“…On contrastenhanced MR imaging, Geng et al [4] noted that none of the lesions showed contrast enhancement on all phases. However, other studies have reported that thin rimenhancement may be seen due to the fibrous capsule [6], such as in our case.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…On contrastenhanced MR imaging, Geng et al [4] noted that none of the lesions showed contrast enhancement on all phases. However, other studies have reported that thin rimenhancement may be seen due to the fibrous capsule [6], such as in our case.…”
Section: Discussioncontrasting
confidence: 50%
“…On contrast-enhanced CT, solitary necrotic nodules usually present as well-defined low-or iso-attenuated nodules. Usually, the lesions show no contrast-enhancement, but thin rim-enhancement may be seen [6]. The lesion may also have calcifications [7].…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted MRI could have been done in order to investigate this nodule, and is nowadays performed more frequently in our centre. An alternate differential diagnosis would be of a necrotic nodule but distinction from a CRCLM is sometimes difficult [ 13 ]. Intraoperative ultrasound displayed a hyperechoic mass in segment 8, which is unusual in colorectal liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…IPT and SNN can also present as HHN. Twenty-seven IPT and SNN in our study appeared to be heterogeneous, with mixed or patchy high signals on T2WI, which resulted from liquefaction or fibrosis in the nodule 11 . In our study, mild hyperintensity appeared only in IPT and SNN.…”
Section: Discussionmentioning
confidence: 60%